Why are East Asians more susceptible to several infection-associated cancers (carcinomas of the nasopharynx, stomach, liver, adenocarcinoma of the lung, nasal NK/T-cell lymphomas)? - Wee, J. (2016)
10.1016/j.mehy.2012.09.003